The role of character strengths in teachers’ mental health: Contributions of positive psychology - Costa, Rodney Querino Ferrereira da; Galhardo, Priscila Bonato; Caetano, Luciana Maria; Souza, Maria Thereza Costa Coelho de (Seven Editora, 2024)
The mental health of teachers has been the subject of important reflections and discussions, since the lack of professional recognition, low salaries, and overload of functions are among the factors that trigger illness among educators. To this end, Positive Psychology is presented as a source of studies on character strengths, which seek, through virtues, satisfaction with life and well-being. Therefore, the objective of this chapter is to present a narrative review of the literature on the relationships between character strengths and teacher mental health. The researches found showed that character strengths can be resources that help in the challenges of teaching practice and in work relationships. In addition, cultivating or building character strengths can increase levels of happiness and subjective well-being, as well as decrease and prevent aspects of physical and mental burnout in teachers. DOI:https://doi.org/10.56238/sevened2024.001-056